PENGARUH DIAMETER MAGNET DAN SUDUT SERANG MAGNET SERTA INTERAKSINYA TERHADAP GAYA TANGENSIAL PADA TURBIN MAGNET MENGGUNAKAN MAGNET PERMANEN NEODYMIUM: THE EFFECT OF MAGNET DIAMETER AND ANGLE OF ATTACK AND THEIR INTERACTION ON TANGENTIAL FORCES IN MAGNET TURBINES USING NEODYMIUM PERMANENT MAGNETS - Rizqi; Wirawan (Program Studi Teknik Mesin PSDKU Polinema Kediri, 2025)
A turbine is a drive that converts potential energy into kinetic energy and kinetic energy. The nature of magnets with the same poles will result in a repulsive force or a pushing force. The aim of this research is to determine the effect of magnet diameter and magnet attack angle and their interaction on the tangential force in a magnetic turbine using neodymium permanent magnets. The research method used is experimental on a magnetic turbine using neodymium permanent magnets. Variations in the diameter of the magnet are 15 mm, 20 mm, 25 mm, and 30 mm and variations in the angle of attack of the magnet are 5°, 10°, 15°, 20°. The results obtained in this research are that in the clockwise rotation direction the optimal tangential force value is 4.648 N with a magnet diameter of 30 mm and an angle of attack of 5°, while in the counterclockwise rotation direction the optimal tangential force value is 4.087 N with a diameter 30 mm magnet and angle of attack 5°.